CORPUS LINGUISTICS RESEARCH: ANALYZE THE USE OF LINKING VERB IN CNN ARTICLES - Nurfitria, Novita; Indriani, Lilia (Fakultas Ilmu Budaya, Universitas Mulawarman, 2022)
In this article, the researcher discusses present verbs. Present verbs are typically employed in the simple present tense to describe events that occur on a regular basis in the present. This article discusses the use of present verbs in twelve news articles on CNN.com. The goal of this research is to determine how many present verbs are used on CNN.com and which present verbs are most often utilized. I chose CNN.com because CNN.com is one of the largest mass media in the world. Mass media was first initiated by Ted Turner and Reese Schoenfeld and was first launched in 1980 and is a subsidiary of WarnerMedia. It is also the first TV channel to broadcast news 24 hours non-stop. The data is collected using a qualitative method, specifically by collecting news from CNN.com. The review reveals the variety of present verb uses in 57 (fifty-seven) news articles on CNN.com in 2020 and the variety of present verbs that are often utilized.